SMX and front-end board tester for CBM readout chain. (1st April 2022) - Zabołotny, W.M.; Emschermann, D.; Gumiński, M.; Kruszewski, M.; Lehnert, J.; Miedzik, P.; Poźniak, K.; Romaniuk, R.; Schmidt, C.J.
Abstract: The STS-MUCH-XYTER (SMX) chip is a front-end ASIC dedicated to the readout of Silicon Tracking System (STS) and Muon Chamber (MUCH) detectors in the Compressed Baryonic Matter (CBM) experiment. The production of the ASIC and the front-end boards based on it is just being started and requires thorough testing to assure quality. The paper describes the SMX tester based on a standard commercial Artix-7 FPGA module with an additional simple baseboard. In the standalone configuration, the tester is controlled via IPbus and enables full functional testing of connected SMX, front-end board (FEB), or a full detector module. The software written in Python may easily be integrated with higher-level testing software.